The book of lost tales - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Tolkien, Christopher. History of Middle-Earth, 1992)
The Book of Lost Tales stands at the beginning of the entire conception of Middle-Earth and Valinor, for the Tales were the first form of the myths and legends that came to be called The Simarillion. The second part of The Book of Lost Tales includes the tale of Beren and Luthien, Turin and the Dragon, and the only full narratives of the Necklace of the Dwarves and the Fall of Gondolin.